2018
DOI: 10.1016/j.radcr.2018.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Skin ischemia and ulceration as a complication of inferior phrenic artery embolization for hepatocellular carcinoma

Abstract: Nontarget embolization from transarterial liver-directed therapy for hepatocellular carcinoma is a rare complication. We present a case of flank skin ulceration after embolization of the inferior phrenic artery supplying tumor. This complication of inferior phrenic artery embolization underscores caution when using small particles to embolize extrahepatic supply to hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…There is a pseudoaneurysm at the anterior aspect of the knee joint arising from the inferior lateral geniculate artery (short arrow). b There is successful occlusion of the pseudoaneurysm following coil embolization (2 x Ruby coils, 3 mm × 5 cm and 4 mm × 6 cm) of the feeding artery 300 μm, a phenomenon also reported in other anatomical sites (Koh et al 2018;Khoury et al 2017). Three patients in our cohort underwent embolization with gelatin foam-based slurry (Gelfoam; Pfizer).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…There is a pseudoaneurysm at the anterior aspect of the knee joint arising from the inferior lateral geniculate artery (short arrow). b There is successful occlusion of the pseudoaneurysm following coil embolization (2 x Ruby coils, 3 mm × 5 cm and 4 mm × 6 cm) of the feeding artery 300 μm, a phenomenon also reported in other anatomical sites (Koh et al 2018;Khoury et al 2017). Three patients in our cohort underwent embolization with gelatin foam-based slurry (Gelfoam; Pfizer).…”
Section: Discussionmentioning
confidence: 57%
“…Particles smaller than this were generally avoided due to their potential to contribute to cutaneous ischemia. Increased rates of skin erythema or necrosis were reported in a systematic review by Kolber et al with particles less than 300 μm, a phenomenon also reported in other anatomical sites (Koh et al 2018 ; Khoury et al 2017 ).…”
Section: Discussionmentioning
confidence: 62%
“…cTACE is applied in clinical practice with a longer period than DEB-TACE, thus articles focusing on the TACE of EHC blood supplies are limited to cTACE. [12][13][14][15] In the other words, the role of DEB-TACE in the treatment of EHC blood supplies of HCC is still undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no grade 3-4 liver toxicity was documented in all patients in our study, indicating that TACE of EHC arteries is safe with regard to liver function. The safety of transarterial management for HCC with the IPA has been evaluated in several studies, [12][13][14][15] and most of the adverse events were pulmonary complications, of which fewer than 5% met the definition for major complications. 13 In our study, DEB-TACE and cTACE showed no significant difference in both major and minor complications.…”
mentioning
confidence: 99%